(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Different variants of reorganization changes, the role and importance of transitional balances and other forms of statements and their implementation have been considered. The main procedures related with the formation of such statements in the period of merge, distribution of enterprises, transfer them to other legal forms have been disclosed. Suggestions concerning the specifics of display the operations of property transactions, capital and liabilities at the statements have been given. At the theory of balance keeping proposed to allocate a separate group of reorganization balances, which are consist of: unification (consolidated), distribution, transformation, and also the zero and the liquidation balances. It is advisable to develop and adopt a specific provision or guidelines for disclosure the basic principles and rules for reporting the reorganization of enterprises.